Analisis Spasial Penentuan Tipe Iklim Menurut Klasifikasi Schmidt-Ferguson Menggunakan Metode Thiessen-Polygon Di Kabupaten Bojonegoro Berdasarkan Data Curah Hujan Tahun 2016–2022 - Hidayat, Alyi Savitri Astriyani; Baskoro, Winardi Tjahyo; Unsuriyah, Zumrotul; Yuliara, I Made; Widagda, I Gusti Agung; Pramarta, Ida Bagus Alit; Kurnia, Wenas Ganda (Universitas Hamzanwadi, 2023)
Research on Schmidt-Ferguson climate classification and Thiessen polygon mapping in Bojonegoro Regency, East Java has been carried out based on rainfall data during the 2016–2022 period. The aim of this research is to determine climate types according to the Schmidt-Ferguson classification and the spatial distribution of climate types using the Thiessen Polygon method in Bojonegoro Regency, East Java. This process begins with collecting rainfall data, coordinates and height of rain posts. From the analysis results obtained, Bojonegoro Regency has 4 types of climate based on the Schmidt-Ferguson classification, namely: Very Wet (A), Wet (B), Slightly Wet (C) and Dry (F). While based on Thiessen Polygon mapping, type A distribution has an area of 323.02 km2, climate type B classification covering an area of 962.22 km2, Classification of climate type C covering an area of 669.95 km2 and climate type F classification covering an area of 374.07 km2.